Maternal race, demography and health care disparities impact risk for IVH in preterm neonates - Shankaran, Seetha (2014)
OBJECTIVE: To determine whether risk factors associated with Grade (Gr) 2–4 intraventricular hemorrhage (IVH) differs between African ancestry and white subjects. STUDY DESIGN: Inborn, appropriate for gestational age (GA) infants with birth weights (BW) 500–1250 grams and exposed to >1 dose of antenatal steroids were enrolled in 24 neonatal intensive care units. Cases had Gr 2–4 IVH and controls matched for site, race and BW range had 2 normal ultrasounds read centrally. Multivariate logistic regression modeling identified factors associated with IVH across African ancestry and white race. RESULTS: Subjects included 579 African ancestry or white race infants with Gr 2–4 IVH and 532 controls. Mothers of African ancestry children were less educated, and white case mothers were more likely to have > 1 prenatal visit and have a multiple gestation (P ≤.01 for all). Increasing GA (P =.01), preeclampsia (P < .001), complete antenatal steroid exposure (P = .02), cesarean delivery (P < .001) and white race (P = .01) were associated with decreased risk for IVH. Chorioamnionitis (P = .01), Apgar< 3 at 5 min (P < .004), surfactant (P < .001) and high frequency ventilation (P < .001) were associated with increased risk for IVH. Among African ancestry infants, having >1 prenatal visit was associated with decreased risk (P = .02). Among white infants, multiple gestation was associated with increased risk (P < .001) and higher maternal education with decreased IVH risk (P < .05). CONCLUSION: Risk for IVH differs between African ancestry and white infants and may be attributable to both race and health care disparities.